Psychological empowerment and job performance: Examining serial mediation effects of self-efficacy and affective commitment - Paola Ochoa Pacheco; David Coello-Montecel; Michelle Tello (Administrative Sciences, 2023)
A substantial body of literature has analyzed the influence of psychological empowerment on individual and organizational outcomes. However, there is still a need to examine how empowered employees achieve higher performance. To fill this gap in the literature, this study analyzed the mediating role of self-efficacy and affective commitment in the relationship between psychological empowerment and task-based job performance. Data were collected from 357 employees. The hypotheses were tested using structural equation modeling and bootstrapping procedures. The results validated the structural relationships between psychological empowerment, self-efficacy, affective commitment, and task-based job performance. In addition, the serial mediation effect of self-efficacy and affective commitment was also confirmed. These results highlight the relevance of psychological variables, such as psychological empowerment and affective commitment, for individuals and organizations. The study supports that feeling empowered and emotionally committed is essential in building a long-term relationship between the employee and the organization.
Keywords: 350; affective commitment; job performance; psychological empowerment; self-efficacy; serial mediation analysis